2015
DOI: 10.5152/tjg.2014.5592
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standard and standard plus vitamin E therapy for Helicobacter pylori eradications in children

Abstract: Background/Aims: Although various drugs can be used in adults for Helicobacter pylori eradication in adults, treatment options are limited in children. The aim of this study was to compare the effects of the standard lansoprazole, amoxicillin, and clarithromycin (LAC) protocol to those of LAC + vitamin E (LACE) combination for H. pylori eradication. Materials and Methods: The study included 90 children (age range: 10-17 years) who were admitted to four pediatric gastroenterology centers between March 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The overall eradication rate of 73.6% is similar to the rates reported in previous studies [11][12][13][14][15][16] but well below the greater than 90% optimal eradication cut-off for H. pylori therapies. 7 Multiple factors may contribute to eradication failure, including inadequate patient adherence to treatment protocol and increasing resistance rates to commonly prescribed antimicrobials.…”
Section: Discussionsupporting
confidence: 85%
“…The overall eradication rate of 73.6% is similar to the rates reported in previous studies [11][12][13][14][15][16] but well below the greater than 90% optimal eradication cut-off for H. pylori therapies. 7 Multiple factors may contribute to eradication failure, including inadequate patient adherence to treatment protocol and increasing resistance rates to commonly prescribed antimicrobials.…”
Section: Discussionsupporting
confidence: 85%
“…A recent review of primary antimicrobial resistance in H. pylori in Turkey demonstrated resistance rates to amoxicillin, clarithromycin, and metranidazole of 0.97%, 24.8%, and 33.7%, respectively (27). In previous years, clarithromycin resistance rate was reported to be 18 -22 % in children (3,28), but recent studies demonstrated an increased clarithromycin resistance rates (42-53%) in our country (29,30). In our study, primary clarithromycin resistance rate was 52.6% similar to the recent reports.…”
Section: 7% Of Children After Successful Eradicationmentioning
confidence: 70%